2015
DOI: 10.1016/j.meatsci.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties, fatty acid profile and sensory characteristics of sheep and goat meat sausages manufactured with different pork fat levels

Abstract: The effect of three pork backfat levels (0% vs. 10% vs. 30%) on chemical composition, fatty acid profile and sensory properties on sheep and goat meat sausages was studied. All physicochemical parameters were affected by the addition of pork backfat in both types of sausages. Sausages manufactured with 30% of pork backfat showed the lowest moisture and protein contents and the highest total fat content. The lower a w values in sausages manufactured with higher fat content while in pH happened the reverse situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 21 publications
10
43
2
6
Order By: Relevance
“…This meat from animals with very low commercial value is more appropriated to process and cure with salts as some of popular products as Cecina in Spain (Hierro, de la Hoz, & Ordoñez, 2004), or Brazilian Charqui (Madruga & Bressan, 2011) ore in Italy violin di capra (Fratianni, Sada, Orlando, & Nazzaro, 2008). Also with the goal to added value to depreciated meats several authors have recently studied sheep and goat processed products as Polpara, Sornprasitt, and Wattanachant (2008) studying quality characteristics of raw and canned goat meat during storage in water, brine, oil and Thay curry; Das, Anjaneyulu, Thomas, and Kondaiah (2009) studying the effect of different fats on the quality of goat meat patties; Teixeira, Pereira, and Rodrigues (2011) evaluating the effect of salting, air-drying and aging in a new goat meat product "manta"; Oliveira et al (2014) analyzing the quality of ewe and goat meat cured products; Leite et al (2015) and Paulos et al (2015) studying the properties of sheep and goat meat sausages and Tolentino, Estevinho, Pascoal, Rodrigues, and Teixeira (2016) evaluating the microbiological and sensory quality of new meat cured products obtained from sheep and goat meat of culled animals. In this context, a project among a research center (Carcass and Meat Quality and Technology Laboratory of Agriculture Scholl of Polytechnic Institute of Bragança), two breeder associations (ANCRAS -National Breed Producers Association of Serrana Goat and ACOB -National Breed Producers Association of Bragançana Sheep) and a meat manufacturing industry and Bísaro breed producer (Bísaro Salsicharia Tradicional) was developed to add value to animals with very low commercial value and consumer acceptability, processing meat that cannot be commercialized as PDO or IGP products.…”
Section: Introductionmentioning
confidence: 99%
“…This meat from animals with very low commercial value is more appropriated to process and cure with salts as some of popular products as Cecina in Spain (Hierro, de la Hoz, & Ordoñez, 2004), or Brazilian Charqui (Madruga & Bressan, 2011) ore in Italy violin di capra (Fratianni, Sada, Orlando, & Nazzaro, 2008). Also with the goal to added value to depreciated meats several authors have recently studied sheep and goat processed products as Polpara, Sornprasitt, and Wattanachant (2008) studying quality characteristics of raw and canned goat meat during storage in water, brine, oil and Thay curry; Das, Anjaneyulu, Thomas, and Kondaiah (2009) studying the effect of different fats on the quality of goat meat patties; Teixeira, Pereira, and Rodrigues (2011) evaluating the effect of salting, air-drying and aging in a new goat meat product "manta"; Oliveira et al (2014) analyzing the quality of ewe and goat meat cured products; Leite et al (2015) and Paulos et al (2015) studying the properties of sheep and goat meat sausages and Tolentino, Estevinho, Pascoal, Rodrigues, and Teixeira (2016) evaluating the microbiological and sensory quality of new meat cured products obtained from sheep and goat meat of culled animals. In this context, a project among a research center (Carcass and Meat Quality and Technology Laboratory of Agriculture Scholl of Polytechnic Institute of Bragança), two breeder associations (ANCRAS -National Breed Producers Association of Serrana Goat and ACOB -National Breed Producers Association of Bragançana Sheep) and a meat manufacturing industry and Bísaro breed producer (Bísaro Salsicharia Tradicional) was developed to add value to animals with very low commercial value and consumer acceptability, processing meat that cannot be commercialized as PDO or IGP products.…”
Section: Introductionmentioning
confidence: 99%
“…Paulos et al (2015) reported that goat meat fresh sausages were defined as harder and more fibrous than the ones made of mutton and concluded that fresh sausages made of the meat of culled goats can be marketable. Good acceptability of fresh sausages made of the meat of culled goats and 30% of pork fat was also reported by Leite et al (2015).…”
Section: Consumersmentioning
confidence: 78%
“…Good acceptability of fresh sausages made of the meat of culled goats and 30% of pork fat was also reported by Leite et al . ().…”
Section: Resultsmentioning
confidence: 97%
“…Além disso, o óleo de cártamo é uma fonte rica em α-tocoferois, desempenhando assim potente ação antioxidante (CAMPANELLA et al, 2014). Leite et al (2015) estudaram as propriedades físico-químicas, perfil de ácidos graxos e características sensoriais de salsichas de ovino e caprino fabricados com diferentes porcentagens de gordura suína, usando o grupo controle (sem adição de gordura), 10% e 30% de gordura suína. Todos os parâmetros físico-químicos foram afetados pela adição em ambos os tipos de salsichas.…”
Section: Resultsunclassified